2019
DOI: 10.1038/s41564-019-0481-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for phospholipid export from the bacterial inner membrane by the Mla ABC transport system

Abstract: The Mla pathway is believed to be involved in maintaining the asymmetrical Gramnegative outer membrane via retrograde phospholipid transport. The pathway is composed of 3 components: the outer membrane MlaA-OmpC/F complex, a soluble periplasmic protein, MlaC, and the inner membrane ATPase, MlaFEDB complex. Here we solve the crystal structure of MlaC in its phospholipid free closed apo conformation, revealing a pivoting βsheet mechanism which functions to open and close the phospholipid-binding pocket. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
158
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(175 citation statements)
references
References 90 publications
8
158
2
Order By: Relevance
“…The Mla pathway may function either to maintain outer membrane homeostasis/asymmetry (retrograde transport) 19,20,22,23 or to export nascent phospholipids to the outer membrane (anterograde transport) 21,27 . In both cases, one might predict that higher levels of Mla transport activity will be required during conditions of rapid growth or envelope stress, while transport needs may be minimal when growth is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mla pathway may function either to maintain outer membrane homeostasis/asymmetry (retrograde transport) 19,20,22,23 or to export nascent phospholipids to the outer membrane (anterograde transport) 21,27 . In both cases, one might predict that higher levels of Mla transport activity will be required during conditions of rapid growth or envelope stress, while transport needs may be minimal when growth is limited.…”
Section: Discussionmentioning
confidence: 99%
“…to the OM as the cell grows 21,27 , and the direction of lipid transport mediated by Mla remains to be firmly established.…”
mentioning
confidence: 99%
“…In addition, the protein may carry simultaneously two PL with different head groups. Considering recent studies 29, 31 , the structural signatures of the ATPase and permease models from the ortholog Mla system in E. coli 26 , characteristic of importer and exporter ABC cassettes, we propose, in addition to the aforementioned role in retrograde phospholipid trafficking, a second potential mode of action as an anterograde trafficking system (dashed lines) that would contribute to the maintenance of phospholipid distribution asymmetry.…”
Section: Discussionmentioning
confidence: 91%
“…A countercurrent model would explain how asymmetries in lipid distribution in the two membranes might be achieved 54 . Although genetic and functional evidences have mainly suggested that the Ttg2/Mla pathway is a retrograde transport system 19, 55, 56 , recent studies in E. coli have shown that MlaD spontaneously transfers phospholipids to MlaC in vitro 31, 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation